Bush imperator : guerre du Golfe et "nouvel ordre mondial" - Jaber, Salah; Jaber, Salah; Serfaty, Abraham; Warshawski, Michel; Weksler, Marcello (Montreuil: La Brèche, 1991)
"sous la direction de Salah Jaber Bibliotheek François Vercammen"